Case report: Complete response to pembrolizumab in a liver metastatic colon adenocarcinoma patient with a novel likely pathogenic germline MSH2 mutation - Xu, Yanjie; Li, Qin; Zhao, Jiemin; Ni, Xuefeng; Li, Ping; Hu, Wenwei (Frontiers in Immunology, 2022)
Lynch syndrome (LS) is a genetic disorder mainly caused by germline mutations in mismatched repair (MMR) genes (MSH2, MLH1, MSH6, and PMS2) or deletions of the epithelial cell adhesion molecule gene (EPCAM). A 43-year-old Chinese male patient underwent radical surgery and was pathologically confirmed to have stage IIIB colon adenocarcinoma. After four cycles of standard adjuvant chemotherapy, the tumor reoccurred in situ with intestinal obstruction. The patient received secondary colectomy. Immunohistochemistry analysis revealed a loss of MSH2 protein expression in the surgical specimen. Noticing that the patient’s mother and grandfather all were diagnosed with LS-related cancers, we collected the patient’s and his mother’s peripheral blood for genetic testing, and the result showed a six-base deletion of MSH2. Thus, we concluded that our patient had LS. Subsequently, the patient accepted pembrolizumab as the first-line systemic therapy after liver metastases. He achieved clinical complete response (cCR) within 2 months and remained progression-free for more than 2 years. The case report showed that MSH2 mutation (c.489_494deTGGGTA) is a likely pathogenic mutation, and immunotherapy (pembrolizumab) is effective for this patient.